2013
DOI: 10.1371/journal.pone.0061749
|View full text |Cite
|
Sign up to set email alerts
|

Primary Breast Cancer Tumours Contain High Amounts of IgA1 Immunoglobulin: An Immunohistochemical Analysis of a Possible Carrier of the Tumour-Associated Tn Antigen

Abstract: The Tn antigen (GalNAc alpha-O-Ser/Thr) as defined by the binding of the lectin, helix pomatia agglutinin (HPA) or anti-Tn monoclonal antibodies, is known to be exposed in a majority of cancers, and it has also been shown to correlate positively with the metastatic capacity in breast carcinoma. The short O-glycan that forms the antigen is carried by a number of different proteins. One potential carrier of the Tn antigen is immunoglobulin A1 (IgA1), which we surprisingly found in tumour cells of the invasive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
2
27
1
Order By: Relevance
“…FFPE primary BCa specimens were probed with sheep polyclonal anti-IgA1 and, in common with the recent report by Welinder et al [41], all the samples showed reactivity with the antibody, confirming the presence of IgA1 in these tissues (figure 1). Protein preparations from the same tumour tissues were separated by SDS-PAGE and western blotted and probed with the same anti-IgA1 antibody, verifying the findings of the immunochemistry (figure 1).…”
Section: Iga1 Breast Tissue Immunochemistry and Protein Separationsupporting
confidence: 83%
“…FFPE primary BCa specimens were probed with sheep polyclonal anti-IgA1 and, in common with the recent report by Welinder et al [41], all the samples showed reactivity with the antibody, confirming the presence of IgA1 in these tissues (figure 1). Protein preparations from the same tumour tissues were separated by SDS-PAGE and western blotted and probed with the same anti-IgA1 antibody, verifying the findings of the immunochemistry (figure 1).…”
Section: Iga1 Breast Tissue Immunochemistry and Protein Separationsupporting
confidence: 83%
“…To our best knowledge, anomalies of IgA N-glycopeptides have not yet been described in sera of cancer patients, although aberrantly O-glycosylated IgA carrying the Tn antigen was recently described in breast tumor tissue. 24 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Tn antigen has little or no expression in normal adult tissues. In many types of cancers, including lung adenocarcinomas , cervical cancer , colorectal carcinomas , gastric carcinomas , and breast carcinomas , the expression of Tn antigen is correlated with metastatic potential and poor prognosis. The role of Tn antigen in the development of cancer remains unclear.…”
Section: Relationship Between Tn Antigen and Tumor Cellsmentioning
confidence: 99%